Answer:
y=a(x^2-5x+4)
Explanation:
I mean there are a bunch of answers. to figure it out, you can use the formula where you have solved the zeroes in terms of x.
y=(x-1)(x-4)
y=x^2-5x+4
Now if you add any a value to this function, your function will stretch or compress accordingly
y=a(x^2-5x+4)
So there isn't a single correct answer, but if you're looking for a bunch, then just replace the a value with whatever value you want, you'll still get the same answer since they're all proportional to one another.